Peran Orang Tua Kristen dalam Pembentukan Karakter Anak Menghadapi Degradasi Moral di Sekolah Menengah Atas Negeri 7 Pontianak - Urbanus, Urbanus (Jurnal Kala Nea, 2020)
Abstract: This paper aims to discuss the role of Christian parents in shaping the character of children facing moral degradation. The current phenomenon of children's delinquency leads to moral degradation. This is evident in the fact that children are no longer victims but also perpetrators. The emergence of cases of vandalism, brawl, harassment, rape and even murder committed by children, shows the weakness of moral education in Indonesia. There are two main factors that influence the internal and external. Therefore there is a need for synergy between parents, teachers and the community to educate children. In addition to moral education in the family and community, the school is a partner of parents to educate and instill moral values for children in school. Parents have a big part in shaping the character of children to become moral individuals. This research is here to help parents by offering steps to be able to teach moral values to children. The author uses descriptive methods so that readers can see a picture of the results of research as a whole. The role of parents to overcome the moral degradation of children in the family includes education from the mother's womb, the way a child learns in the family and the five stages of acquisition of values and behavior.